2022
DOI: 10.3390/jcm11216407
|View full text |Cite
|
Sign up to set email alerts
|

Vasoplegic Syndrome after Cardiopulmonary Bypass in Cardiovascular Surgery: Pathophysiology and Management in Critical Care

Abstract: Vasoplegic syndrome (VS) is a common complication following cardiovascular surgery with cardiopulmonary bypass (CPB), and its incidence varies from 5 to 44%. It is defined as a distributive form of shock due to a significant drop in vascular resistance after CPB. Risk factors of VS include heart failure with low ejection fraction, renal failure, pre-operative use of angiotensin-converting enzyme inhibitors, prolonged aortic cross-clamp and left ventricular assist device surgery. The pathophysiology of VS after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 148 publications
0
13
0
Order By: Relevance
“…Shorter CPB time in sildenafil group may translate into lower risk of postoperative vasoplegic syndrome, which is a common etiology of distributive shock following cardiovascular surgery with CPB. 20,22,23 Albeit not statistically significant, lower incidence of PH crisis in the sildenafil group (3 vs 7%) may also reduce the need of prolonged intensive care and monitoring. Our study results were also in line with Nemoto et al , who noted the effectiveness of sildenafil in pediatric patients with persistent pulmonary hypertension following congenital heart surgery; in such cases, sildenafil may be an effective alternative to inhaled nitric oxide due to its minimal systemic side effects.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Shorter CPB time in sildenafil group may translate into lower risk of postoperative vasoplegic syndrome, which is a common etiology of distributive shock following cardiovascular surgery with CPB. 20,22,23 Albeit not statistically significant, lower incidence of PH crisis in the sildenafil group (3 vs 7%) may also reduce the need of prolonged intensive care and monitoring. Our study results were also in line with Nemoto et al , who noted the effectiveness of sildenafil in pediatric patients with persistent pulmonary hypertension following congenital heart surgery; in such cases, sildenafil may be an effective alternative to inhaled nitric oxide due to its minimal systemic side effects.…”
Section: Discussionmentioning
confidence: 85%
“…18 Additionally, sildenafil's wellestablished safety profile in pediatric populations further supports its use as a reliable and safer alternative to other pulmonary vasodilators. 19,20 A randomized controlled trial by Namachivayam et al also demonstrated the benefits of sildenafil in abolishing PH rebound associated with iNO withdrawal and shortening mechanical ventilation time and ICU length of stay. 21 Our study suggested that preoperative sildenafil administration significantly reduced PAP and PA/Ao ratio in pediatric patients with CHD and PH undergoing surgical repair.…”
Section: Discussionmentioning
confidence: 99%
“…This information is continuously stored on the computer and can be later replayed for o ine reevaluation. The system was evaluated at our clinic comparing CBF values measured by the QuantixND® compared with rCBF values [31][32][33][34][35] . We measured the ow volume in the internal carotid artery (ICA) since it was shown that the ow volume has an almost linear correlation with the cerebral blood ow on the measured side 31 but showed an even better correlation when ow volume in both ICA was measured and compared to global CBF 31 .…”
Section: Therapeutical Intervention Und Cbf Monitoringmentioning
confidence: 99%
“…18 Similarly, the use of methylene blue, hydroxocobalamin, or angiotensin II could be of interest in this population but, up to now, efficacy of these therapies has only been substantiated by cases reports. 10,[19][20][21][22][23]…”
Section: Management Of Vasoplegiamentioning
confidence: 99%
“…7,9 The pathophysiology of vasoplegic syndrome remains poorly understood, but it could be associated with cytokine release, adrenergic receptor desensitization, increased nitric oxide synthesis, relative deficiency of vasopressin, activation of adenosine triphosphate–sensitive potassium channels, vascular smooth muscle cell membrane hyperpolarization, dysfunction of the renin–angiotensin system, and endothelial glycocalyx alteration. 10…”
Section: Hemodynamic Managementmentioning
confidence: 99%